TELA’AH METODE PEMBELAJARAN DAN TANTANGAN PEMBELAJARAN ILMU PENGETAHUAN SOSIAL KURIKULUM 2013 DAN KURIKULUM MERDEKA - Muhammad Rahmat Alwafi; Desy Safitri; Sujarwo Sujarwo (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study evaluates transdisciplinary learning methods and challenges in Social Sciences (IPS) learning in the 2013 Curriculum and the Independent Curriculum. This method emphasizes the integration of concepts from different social science disciplines, applied holistically. The challenge of implementing this method in both curricula, involves teacher readiness, availability of resources, and student understanding. The 2013 curriculum emphasizes cross-subject integration, while the Merdeka Curriculum provides flexibility for teachers. Qualitative research involves analysis of documents, literature, and interviews with social studies teachers. The research findings provide insight into the potential and barriers of transdisciplinary methods in both curricula, with implications for teacher skills development, resource improvement, and better understanding to improve social studies learning effectiveness.